Secure cyber-physical systems for smart cities - Shaikh, Riaz Ahmed, 1981- (Information Science Reference, an imprint of IGI Global, 2019)
"This book covers discussion on new security frameworks, solutions, cybersecurity laws and regulations, and risk management frameworks for a smart city environment. It also provides the recent advances in a smart city security and privacy and how to design and implement safe, secure and reliable smart city project"--